2015
DOI: 10.1007/s12237-015-9959-x
|View full text |Cite
|
Sign up to set email alerts
|

Generalist and Specialist Feeding Crabs Maintain Discrete Trophic Niches Within and Among Estuarine Locations

Abstract: Intertidal crabs are abundant, key components of tropical estuaries whose trophic interactions provide a direct and identifiable link within the ecosystem. Our study investigated spatial variability in food resource use of intertidal crabs, using stable isotope (δ 13 C and δ 15 N) values. This was done for two genera with contrasting feeding strategies (specialist Uca vs. generalist Metopograpsus) within and among locations in North Queensland, Australia. Uca coarctata, Uca seismella, Metopograpsus frontalis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 59 publications
(80 reference statements)
0
9
0
Order By: Relevance
“…Thus, more extensive research on the spatial and temporal variability of the origin of basal resources, as well as the bottom-up interactions of estuarine food webs and their relationships with other environmental factors, is needed to better understand the food web dynamics in both systems. Understanding the trophic interactions present in estuaries with a strong human presence is crucially important for defining proper management and conservation strategies 80 . Furthermore, the management of factors that influence an estuary, such as freshwater discharges and urban and agricultural wastes, can regulate inputs of basal resources and modulate a phytoplankton or detrital dominated food web.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, more extensive research on the spatial and temporal variability of the origin of basal resources, as well as the bottom-up interactions of estuarine food webs and their relationships with other environmental factors, is needed to better understand the food web dynamics in both systems. Understanding the trophic interactions present in estuaries with a strong human presence is crucially important for defining proper management and conservation strategies 80 . Furthermore, the management of factors that influence an estuary, such as freshwater discharges and urban and agricultural wastes, can regulate inputs of basal resources and modulate a phytoplankton or detrital dominated food web.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that inter‐tidal crabs also occupy discrete habitats according to environmental conditions related, for instance, to availability of structural complexity (Vermeiren & Sheaves ), generalist or specialized diet (Vermeiren et al . ) or food distribution (Silva et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…might reflect the more omnivorous diet and higher trophic position (including opportunistic carnivory) compared to the elongated claws of Tubuca spp. which often feed on microphytobenthos and scoop up mud rather than crush prey (Vermeiren et al 2015). Freire et al (1996) identified that the portunid L. navigator, with a diet composed mainly of sea weeds and soft organisms, had less mobile chela with lower muscle ratios compared to the portunid L. depurator which consumed more hard-shelled prey.…”
Section: Habitat Characteristics-morphology Linkagesmentioning
confidence: 99%
“…Freire et al (1996) identified that the portunid L. navigator, with a diet composed mainly of sea weeds and soft organisms, had less mobile chela with lower muscle ratios compared to the portunid L. depurator which consumed more hard-shelled prey. Vermeiren et al (2015) studying spatial variation in diet preferences among intertidal mangrove crabs identified that M. frontalis and Metopograpsus latifrons displayed a more opportunistic diet preference, able to shift among locations, compared to the specialized diet of T. coarctata and T. seismella. However, whether this diet opportunism among locations is also evidenced in spatial variation in claw morphologies is not yet known.…”
Section: Habitat Characteristics-morphology Linkagesmentioning
confidence: 99%